If i were to factor 9x+18/3 would it be 9(x+2)?

9x+18/3 = 9x+6 = 3(3x+2) Did you mean (9x+18)/3 ? The parentheses change the meaning of the expression. (9x+18)/3 = 3x+6 = 3(x+2)

9x + (18/3) = 9x + 6 = 3(3x + 2)

(9x + 18)/3 = 9(x + 2)/3 =3(x +2)

Name*

E-Mail*

Comment*

Prev Questions

Next Questions

## Answers

9x+18/3 = 9x+6 = 3(3x+2)

Did you mean (9x+18)/3 ? The parentheses change the meaning of the expression.

(9x+18)/3 = 3x+6 = 3(x+2)

9x + (18/3) = 9x + 6 = 3(3x + 2)

(9x + 18)/3

= 9(x + 2)/3

=3(x +2)